Effect of Fibers on Some Engineering Properties of Cement and Lime Stabilized Soils - Suhail A. Khattab; Ibrahim M. Al-Kiki; Abderrahmane H. Al-Zubaydi (Engineering and Technology Journal, 2011)
Recently, many attempts were made to use metal fiber reinforcements to improve some soil properties. In this research, the effects of fibers on the compaction and mechanical properties of cement and lime stabilized soils (silty and clayey soils respectively) were studied. Variables such as stabilizer (cement and lime) content, amount and type of metal fibers were studied. Results indicated that the addition of fibers lead to increase in the maximum dry unit weight. On the other hand, a maximum values of unconfined and tensile strength were obtained with the addition of 0.5 % short fiber (FS) and 1.5 % long fiber (FL) respectively. During the flexural test a brittle manner failure was observed for the unreinforced samples and samples prepared with little amount of fibers 0.5%. Finally, the addition of fibers increases the fracture energy of cement stabilized silty soil and lime stabilized clayey soil.